Assembly of Oriented Ultrafine Polymer Fibers by Centrifugal Electrospinning. (19th November 2013) - Liu, Shu-Liang; Long, Yun-Ze; Zhang, Zhi-Hua; Zhang, Hong-Di; Sun, Bin; Zhang, Jun-Cheng; Han, Wen-Peng
Abstract : Uniaxially aligned and cross-aligned arrays of ultrafine polymer fibers have been fabricated by a novel and effective centrifugal electrospinning setup with rotating polymer solution jets. Comparing with conventional electrospinning (10–30 kV) and centrifugal spinning (4, 000–12, 000 rpm), this technique only requires a lower working voltage (2.8–6.0 kV), a slower rotational speed (360–540 rpm), and a shorter spinning distance (2.0–4.0 cm). In addition, the influences of experimental parameters such as working voltage, rotational speed, collecting distance, and solution concentration on the alignment of the as-spun fibers are investigated using image analysis techniques. It is found that the working voltage and rotational speed mainly influence the perpendicular and linear velocities of the fibers, respectively. The polymer fibers tend to show higher alignment degree when these two velocities are very close. Optimum conditions (working voltage 3.0 kV, rotational speed 420 rpm, collecting distance 2.5 cm, and solution concentration 18 wt%) to maximize alignment degree ( ~ 97%) of polystyrene fibers are also obtained.